Contribution to the flora of Asian and European countries: new national and regional vascular plant records, 6. Issue 1 (2nd January 2017) - Nobis, Marcin; Erst, Andrey; Nowak, Arkadiusz; Shaulo, Dmitry; Olonova, Marina; Kotukhov, Yuriy; Doğru-Koca, Asli; Dönmez, Ali A.; Király, Gergely; Ebel, Aleksandr L.; Kushunina, Maria; Piwowarczyk, Renata; et al.
Abstract: The paper presents new records for 28 vascular plant species from 14 Eurasian countries. Five taxa ( Catabrosa capusii, Poa albertii, Poa intricata, Poa pseudoaltaica, Poa sergievskajae ) are reported from Kazakhstan, three ( Ranunculus pseudomonophyllus, Ranunculus smirnovii, Ranunculus turczaninovii ) from Mongolia, three ( Panicum barbipulvinatum, Stipa eriocaulis, Tragopogon pratensis subsp . minor ) from Poland, three ( Euphorbia subtilis, Corydalis grubovii, Thymus callieri ) from Russia, two ( Atriplex ornata, Corispermum dutreuilii ) from Afghanistan, two ( Orobanche grenieri, Ranunculus mongolicus ) from Kyrgyzstan, two ( Erigeron annuus, Sternbergia lutea ) from Tajikistan, two ( Orobanche baumanniorum, Orobanche kotschyi ) from Turkey, one ( Polygonum subaphyllum ) from China, one ( Orobanche bartlingii ) from Georgia, one ( Rubus slavonicus ) from Germany, one ( Cenchrus spinifex ) from Montenegro, one ( Rubus canadensis ) from Slovenia and one ( Bolboschoenus yagara ) from Switzerland. For each species, synonyms, general distribution, habitat preferences, taxonomy with remarks on recognition and differentiation of the species from the most similar taxa occurring in a given country as well as a list of recorded localities (often far from the previously known areas) are presented.